Analisis Pengaruh Ads Intrusiveness dan Ads Irritation Terhadap Ads Avoidance Melalui Attitude Toward Ads Sebagai Variabel Mediasi di Platform Tiktok - Muhammad Alfatih; Andi Muhammad Sadat; Shandy Aditya (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
Based on the results of the study on the influence of Ads Intrusiveness and Ads Irritation on Ads Avoidance through Attitude Toward Ads as a mediating variable on the TikTok platform, the conclusions that can be drawn are as follows: Overall, this study shows that emotional factors such as irritation play a significant role in driving ads avoidance, while intrusiveness tends to influence attitude toward ads more than directly encouraging users to avoid advertisements. Attitude toward ads is also proven to be an important factor in explaining user behavior toward advertisements on the TikTok platform.